Key participants in combating terrorism. - McDonald, M.D.
Four recommendations are made to optimize the role of American citizens and their communities in homeland security and other societal functions being shaped in association with homeland security. These four recommendations are centered on democratic principles that would engage the public more directly in homeland security and a public health response to reduce the probability of deaths, negative health effects, and other adverse outcomes associated with asymmetric warfare. They cover: public health surveillance and maintaining fundamental rights; risk communications, citizen decision-making, and martial law; community-based health alert systems; and citizens acting together to reduce risks and improve their communities
Keywords: American citizens; Adverse outcomes; Asymmetric warfare; Citizen decision-making.; Combating terrorism; Communities; Community-based health alert systems; Deaths; Democratic principles; Fundamental rights; Homeland security; Martial law; Negative health effects; Public health response; Public health surveillance; Risk communications; Risks; Societal functions